Nghiên cứu xây dựng mô hình nuôi tằm con tập trung - Trịnh, Thị Toản (Trường Đại học Đà Lạt, 2013)
Along time ago, cooperative rearing of young silkworm had been conducted in some countries such as Japan, India, China... In Vietnam, however, it is not pay attention enough.Silkworm rearing duration includes two stages: young silkworm stage (first to third instar) and late age stage (fourth to fifth instar). Cooperative rearing of young silkworm is a solution that helps to improve the most difficult stage - early stage for farmers. If in the early stage silkworm are carefully tended, in the fourth and fifth later they will grow healthily, that is to say, we can expect a good cocoon crop. During 2002 - 2003 years, the authors under Lamdong Agro - Forestry Research and Experiment Center have effectively organized and applied Model of cooperative rearing of young silkworm at two areas with different climatic conditions namely Baoloc and Ductrong.This Model successfully extended with 1500 boxes of young silkworm (a box includes 20gr of eggs) and thousands of farmers. All the rearings obtained high and stable cocoon yield of 40 - 45kg per box. The cocoons have good quality so were sold with good price. Other wide the duration from receiving young silkworm to harvesting of cocoons takes only 18 days instead of 30 days if starting from brushing. Generally, the Model of cooperative rearing of young silkworm is one of the technical solutions that greatly contributes in improvement of cocoon and silk yield and quality.Recently, this advanced technology was officially recognized by Scientific Committee of Ministry of Agriculture and Rural Development and was permitted to apply on large scale in Vietnam.